ACADEMIC SUPERVISION BY SCHOOL PRINCIPALS (MULTISITE STUDY AT SDN SN PELAMBUAN 4 AND SDN MELAYU 2 IN BANJARMASIN CITY) - Dahlia Dahlia; Aslamiah Aslamiah; Metroyadi Metroyadi (LP2M IAI Al-Khairat Pamekasan, 2026)
The principal has the duty as a supervisor. In supervision, the principal has the duty and responsibility to advance teaching through continuous improvement of the teaching profession. The purpose of this study is to analyze in depth the model, approach, and follow-up of the principal's academic supervision at SDN SN Pelambuan 4 and SDN Melayu 2 in Banjarmasin City. This study uses a qualitative approach with a multi-site study design and data collection techniques through interviews, observation, and documentation. The research data sources are the principal and teachers. Data analysis uses descriptive analysis starting with data condensation, data presentation, drawing and verifying conclusions. Data validity checking techniques are carried out through observation and triangulation. The results of this study show that the supervision model implemented using a clinical model through case discussions and traditional with direct classroom observation is able to improve teacher performance and provide effective learning facilities for students through the pre-supervision, supervision, post-supervision or follow-up stages. The academic supervision approach is carried out indirectly through discussions with teachers before and after supervision activities. The collaborative approach has been able to help teachers provide alternative solutions to the problems being faced. The follow-up of academic supervision has been carried out as it should be as a concrete form of improvement and enhancement of the quality of learning and creating competent graduates.